Pendapatan Premi dan Hasil Investasi terhadap Cadangan Dana Tabarru’ Pada Industri Asuransi Syariah Indonesia - Ahmad Subaki; Akhmad H. Abubakar; Faizal Ridwan Zamzany (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2020)
This study aims to determine the effect of premium income and investment returns on tabarru 'reserve funds in life insurance companies in Indonesia. This study, using a correlational method, the population used in this study is a life insurance company that is a member of the Indonesian Sharia Insurance Association (AASI). A sample of 7 (seven) companies, the data collection techniques used were document review, and the data management and analysis techniques used were accounting analysis and multiple linear regression analysis. The results of the coefficient of determination analysis show that the variable premium income and investment returns can explain 92.5% of the variation in the tabarru' reserve fund variable, while the remaining 7.5% is explained by other variables not included in this study. The results showed that partially premium income and investment returns have a positive and significant effect on tabarru 'reserve funds. While simultaneously premium income and investment returns also have a positive and significant effect on tabarru 'reserve funds. Based on the results of the above research, it is suggested to the Islamic life insurance company, which is the sample in the study, if you want to obtain an increased tabarru' reserve fund, then you should do better promotions so that the premium income obtained increases and makes the best possible investment, so that getting investment income (investment returns) is improving.